Kekuatan Hukum Pembuktian Secara Akta Otentik di Tinjau dari Pasal 1868 Kitab Undang-undang Hukum Perdata dalam Proses Sengketa Perdata di Pengadilan - Herlina Basri (Rechtsregel : Jurnal Ilmu Hukum, 2021)
The evidence system relies heavily on how a legal expert provides definitions for each of these evidences. Legal experts will, of course, provide a definition by first defining the meaning of a proof. Some experts express their opinion regarding the meaning of the term system of proof as follows: R. Subekti gives insight in evidence, namely the process of proving and convincing the judge of the truth of the arguments put forward by the parties in a dispute argued the process. Sudikno Mertokusumo takes a different view, namely that what is termed in a legal sense from the context of evidence is an attempt to give judges examining the case in question sufficient ground to provide assurance as to the truth of the proposed legal event. Provable are the events or legal relationships presented by the litigants, the dispute or dispute filed by the party but denied or denied by the other party. Evidence is provisions that provide outlines and guidelines about ways justified by law to prove wrongdoing in a dispute. Evidence is also a provision that regulates evidence that is justified by law and can be used by judges in proving a civil dispute. Evidence in Article 1865 of the Civil Code Evidence is: "Anyone who claims to have a right, or who designates an event to confirm his right or to refute a right of another, is obliged to prove the existence of that right or event which is stated". The proof is based on Article 1868 of the Civil Code which states that "an authentic deed is a deed in the form determined by law, made by or before public officials who have power for that at the place where the deed was made.".